Application of laser-induced breakdown spectroscopy to zirconium in aqueous solution - Ruas, Alexandre; Matsumoto, Ayumu; Ohba, Hironori; Akaoka, Katsuaki; Wakaida, Ikuo (Spectrochimica acta. Part B: Atomic spectroscopy, 2017)
In the context of the Fukushima Dai-ichi Nuclear Power Plant (F1-NPP) decommissioning process, laser-induced breakdown spectroscopy (LIBS) has many advantages. The purpose of the present work is to demonstrate the on-line monitoring capability of the LIBS coupled with the ultra-thin liquid jet sampling method. The study focuses on zirconium in aqueous solution, considering that it is a major element in the F1-NPP fuel debris that has been subject to only a few LIBS studies in the past. The methodology of data acquisition and processing are described. In particular, two regions of interest with many high intensity zirconium lines have been observed around 350nm in the case of the ionic lines and 478nm in the case of atomic lines. The best analytical conditions for zirconium are different depending on the analysis of ionic lines or atomic lines. A low LOD of about 4mgL−1 could be obtained, showing that LIBS coupled with the ultra-thin liquid jet sampling technique is a promising alternative for more complex solutions found in the F1-NPP, namely mixtures containing zirconium. [Display omitted] •Zirconium aqueous solutions were analysed by LIBS with ultra-thin liquid jet.•The best analytical conditions depend on the considered lines (atomic, ionic).•A low limit of detection of about 4mgL−1 was attained.